The rarity of dust in metal-poor galaxies: letter - Fisher, David B.; Bolatto, Alberto D.; Herrera-Camus, Rodrigo; Draine, Bruce T.; Donaldson, Jessica; Walter, Fabian; Sandstrom, Karin M.; Leroy, Adam K.; Cannon, John; Gordon, Karl (Nature, 2014)
Observations of local galaxy I Zw 18 imply that the dust mass in star-forming, metal-poor environments is much lower than expected, and, therefore, that the amount of dust in young galaxies of the early Universe, such as redshift-6.6 galaxy Himiko, is probably a factor of about 100 less than previously thought.
Published: 08 December 2013
Gesehen am 28.09.2021